The biology of chemokines and their receptors - Lira, Sergio A. (2012)
This article summarizes the work done by our laboratory and by our collaborators on the biological role of chemokines and their receptors. Using both gain-of-function and loss of function genetic approaches, we have demonstrated that chemokines are important for the homeostatic distribution of leukocytes in tissues and for their mobilization from the bone marrow. We have also shown that chemokines are important players in inflammation and autoimmunity and that they contribute to lymphoid organogenesis, angiogenesis, and immune regulation. Together, our results and those of the literature suggest an important role for chemokines in homeostasis and disease and characterize chemokines as important targets for therapeutic intervention.